THE QUALITY OF THE NURSING CARE TROUGH A SURGICAL PERIOD ACCORDING TO CLIENTS' FEEDBACK - Vanda M. Galvão Jouclas; Geisa Tavares Tencatti; Vanessa Munhoz de Oliveira (Universidade Federal do Paraná, 1998)
The Quality of the Nursing Care Through a Surgical Period According to Clients' Feedback. This study is part of a project of the Multiprofessional Study Group on Adult Health of the Nursing Department at the UFPR. It aimed at evaluating the quality of the nursing care delivered through a surgical period at a University Hospital in the city of Curitiba, according to the opinion of surgical adult clients. Eight six (86) clients were interviewed, both sexes, who had gone through surgery, capable of personal interaction and voluntary participants of the research. The results demonstrated that the major quality biases occurred during the pre-surgical care period, characterized mostly by minor actions in the expressive field. On the other hand, nursing care at the postoperating room approached the quality standards demanded by the humanistic care.